EFEKTIVITAS KINETIN TERHADAP KUALITAS BENIH KACANG HIJAU FORE BELU YANG MENGALAMI CEKAMAN KEKERINGAN SELAMA FASE GENERATIF - Yosefina Lewar (Politeknik Pertanian Negeri Kupang, 2009)
The research was designed to study the effect of kinetin to and the interaction yield and seed qualityÂ variety mung bean Fore Belu during the drought stress at generative stage. It was conducted from April until September 2007 at Kupang This research was arranged in Completely Randomized Design (CRD) based a factorial experiment (3x4) with three replications. The first factor was soil water content showing the level of drought strees, i.e. soil water content 100% field capacity, soil water content 75% field capacity, and soil water content 50% field capacity. The second factor was the concentration of kinetin i.e. 0, 20, 40 and 60 ppm. Furthermore, the seeds obtained from pot experiment were planted to know quality seeds. Data were analysed using analysis of variance, significant level at 5%, continued with DMRT 5%. The result showed that the drought up to soil water content 75% and 50% field capacity during reproductive stages of variety mung bean Fore Belu decreased yield and seed quality of mung bean. Kinetin sprayed on the leaves was effective to increase yield of mung bean. Concentration 60 ppm of kinetin indicated most the effective concentration to increase the growth and yield of variety mung bean Fore Belu. However concentration 40 ppm have been can give good response to yield of mung bean. Seed quality variety mungbean Fore Belu was not influenced by kinetin giving. A webinar is an online event that is hosted by someone broadcast to a select group of individuals online. (A webinar is sometimes also referred to as a “webcast”, “online event” or “web seminar”.) You should learn about webinar companies here. There was no interaction between drought strees with giving of kinetin to yield and seed quality variety mungbean Fore Belu.Keywords: Kinetin, drought stress, mungbean, generative